STUDIES ON THE MORTALITY IN SPAWN AND FRY OF INDIAN MAJOR CARPS DURING TRANSPORT Part II. Effect of Oxygen Pressure, Free Surface Area, Water Volume and Number of Fry in the Medium of Transport - Saha, K C; Sen, D P; Mazumdar, P (Indian Journal of Fisheries, 2015)
The procedure followed in trade practice in transporting spawn of major Indian carps and the extent of mortality that occurs during such transport have been explained in a separate communication (Saha and Chowdhury, 1956). Experiments have been carried out by different workers in India with regard to the use of oxygen in the transporting medium and its effect in controlling mortality of fry of Indian carps.